Good practice guidelines for agricultural leasing arrangements (Rome, Italy, 2001)
The guidelines therefore deal with the contextual and policy issues surrounding agricultural leasing, but also focus on providing a practical and up-to-date guide and commentary on those issues that need to be considered by both lanlord and tenant when negotiating over the leasing of agricultural land.
Keywords: land use, agricultural,land tenure; law and legislation,law and legislation